Li2O-Reinforced Solid Electrolyte Interphase on Three-Dimensional Sponges for Dendrite-Free Lithium Deposition - Shen, Chao; Yan, Huibo; Gu, Jinlei; Gao, Yuliang; Yang, Jingjing; Xie, Keyu (Frontiers in Chemistry, 2018)
Lithium (Li) metal, with ultra-high theoretical capacity and low electrochemical potential, is the ultimate anode for next-generation Li metal batteries. However, the undesirable Li dendrite growth usually results in severe safety hazards and low Coulombic efficiency. In this work, we design a three-dimensional CuO@Cu submicron wire sponge current collector with high mechanical strength SEI layer dominated by Li2O during electrochemical reaction process. The 3D current collector delivers an enhanced CE of above 91 % for an ultrahigh current of 10 mA cm-2 after 100 cycles, and yields decent cycle stability at 5 C for the full cell. The exceptional performances of CuO@Cu submicron wire sponge current collector holds promise for further development of the next-generation metal-based batteries.